(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2006)
The recent strategic thought requires research and study to indicate the banks suitable which enable them to protect its location in the market and to face the challenges that appeared in the 20 – first century. The research aims at shedding light upon the effect of financial resources growth strategic to a bank loan policy. A questionnaire of ( 30 ) managers, with in different management levels , was used. In order to test hypotheses, the present research has relied upon ( Multiple Regression ) to the influence being exerted at a level ranging between (0.01,0.05,0.10) The analysis of hypotheses also started a number of recommendation that might contribute in rising the standard of applying banking Iraqi sector to protect the organization competitive location in the market.